Status of persistent organic pollutants in Ethiopia - Debela, Sisay Abebe; Sheriff, Ishmail; Daba, Chala; Tefera, Yonatal Mesfin; Bedada, Dinaol; Gebrehiwot, Mesfin (Frontiers in Environmental Science, 2023)
Over the years, the chemical market has shown significant growth, but the hazardous impact of chemical use and disposal on the environment and human health is a growing concern.Persistent organic pollutants (POPs) are among the most dangerous chemicals with widespread effects on the environment and living organisms including humans. This study aimed to assess the current status of POPs management and regulatory infrastructure in Ethiopia by collecting information from stakeholders responsible for recording the import, export, use, management, and regulation of POPs both in government and private sectors.Additionally, a comprehensive literature review was conducted using Boolean operators from international databases and libraries. The results indicated that Ethiopia banned the import of pesticides listed under Annex A (i.e. those to be eliminated) except Endosulfan, which was imported at a quantity of 199,767 kg lt -1 from 2011 to 2015. There are 2,435 PCB-containing transformers in Ethiopia of which 2,242 (92%) are currently in use. These transformers and capacitors contain 1,031,661 kg and 1,255 kg of dielectric fluids, respectively. As for Annex B POPs (i.e. those to be restricted), there are between 928,509 and 1,383,095 kg of active and obsolete Dichlorodiphenyltrichloroethane (DDT) found in different stores across the country.Ethiopia imported approximately 337,000 kg of product containing Perfluorooctane sulfonic acid (PFOS) from 2000 to 2020, with the annual average of 16,850 kg photographic film, paper, and plates. POPs were also detected in different environmental matrices (soil, water bodies, sediments, food items, and air) as well as human blood. Despite these findings, regulation and management of POPs waste and stockpiles is largely inadequate in Ethiopia.Therefore, it is crucial to improve the monitoring, management, and regulation of POPs in the country. This could be achieved by strengthening the collaboration among different SC: Stockholm Convention